2011
DOI: 10.1371/journal.pone.0017809
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus (EBV) Rta-Mediated EBV and Kaposi's Sarcoma-Associated Herpesvirus Lytic Reactivations in 293 Cells

Abstract: Epstein–Barr virus (EBV) Rta belongs to a lytic switch gene family that is evolutionarily conserved in all gamma-herpesviruses. Emerging evidence indicates that cell cycle arrest is a common means by which herpesviral immediate-early protein hijacks the host cell to advance the virus's lytic cycle progression. To examine the role of Rta in cell cycle regulation, we recently established a doxycycline (Dox)-inducible Rta system in 293 cells. In this cell background, inducible Rta modulated the levels of signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…However, the expression of UNG2 was reported to peak in and throughout S phase and then decline to undetectable levels until the next S phase through the ubiquitin-proteasome pathway (61). Taking into account that EBV replication causes cell cycle arrest at the G 1 /S transition without cellular DNA replication (62,63), we suspect the decrease of UNG2 is caused by downregulated transcription or increased protein degradation.…”
Section: Discussionmentioning
confidence: 92%
“…However, the expression of UNG2 was reported to peak in and throughout S phase and then decline to undetectable levels until the next S phase through the ubiquitin-proteasome pathway (61). Taking into account that EBV replication causes cell cycle arrest at the G 1 /S transition without cellular DNA replication (62,63), we suspect the decrease of UNG2 is caused by downregulated transcription or increased protein degradation.…”
Section: Discussionmentioning
confidence: 92%
“…To ensure successful lytic reactivation, EBV modulates various cellular events to facilitate virus production. Some lytic proteins modulate cell cycle progression, such as Rta, which induces G 1 arrest primarily originating at the transcriptional level (6). Some suppress the immune response to facilitate the progression of the viral lytic cycle.…”
mentioning
confidence: 99%
“…This phenomenon is universal in all doxycycline (Dox)-inducible Rta-expressing cell lines, including TW01TetER, 293TetER, and Rta-inducible EBV replication systems in HEK293 cells, dubbed EREV8 ( Fig. 1A and reference 14). Previous studies demonstrated that the consensus Rta binding sites are 16 to 18 nucleotides in length with high GC content, including the two flanking core elements (5=-GNCC-3= and 5=-GGNG-3=) (8)(9)(10).…”
Section: Resultsmentioning
confidence: 83%
“…EBV Rta is known to be a potent transcriptional activator. However, we observed that the expression of Rta efficiently downregulated transcription of a battery of positive cell cycle regulators, including MYC, CCND1, and JUN, effectively leading to cell cycle arrest (14). This phenomenon is universal in all doxycycline (Dox)-inducible Rta-expressing cell lines, including TW01TetER, 293TetER, and Rta-inducible EBV replication systems in HEK293 cells, dubbed EREV8 ( Fig.…”
Section: Resultsmentioning
confidence: 91%